1996
DOI: 10.1006/jcta.1996.0038
|View full text |Cite
|
Sign up to set email alerts
|

On Integral Zeros of Krawtchouk Polynomials

Abstract: We derive new conditions for the nonexistence of integral zeros of binary Krawtchouk polynomials. Upper bounds for the number of integral roots of Krawtchouk polynomials are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 37 publications
0
24
0
4
Order By: Relevance
“…Krawtchouk polynomial [18,20] this can be done in O(n 2 ) time and O(n) space. The basic idea is as follows:…”
mentioning
confidence: 99%
“…Krawtchouk polynomial [18,20] this can be done in O(n 2 ) time and O(n) space. The basic idea is as follows:…”
mentioning
confidence: 99%
“…This conjecture was proved independently by Mignotte and Pethő [14], and by Stroeker and de Weger [16]. When n = 5, Krasikov and Litsyn [10] found a list of zeros: x N ∈ 3 17 14 36 22 67 28 67 133 289 5292 10882 . Hanrot [7] added the zero 24013 48324 to this list and showed that this new list was complete.…”
Section: Zeros Of Q-krawtchouk Polynomialsmentioning
confidence: 88%
“…When n is much larger (growing faster than √ N), Krasikov and Litsyn [10] found a better bound in the binary case:…”
Section: Zeros Of Q-krawtchouk Polynomialsmentioning
confidence: 97%
See 1 more Smart Citation
“…Recall that N is a positive integer, and take k 0 and k 1 such that k 1 , N), see for example [3], are defined by…”
Section: Lemmamentioning
confidence: 99%